Patient and aneurysm factors associated with aneurysm recanalization after coiling. (5th November 2021) - Pierot, Laurent; Barbe, Coralie; Thierry, Aurore; Bala, Fouzi; Eugene, Francois; Cognard, Christophe; Herbreteau, Denis; Velasco, Stéphane; Chabert, Emmanuel; Desal, Hubert; Aggour, Mohamed; Rodriguez-Regent, Christine; et al.
Abstract : Background: One limitation of the endovascular treatment of intracranial aneurysms is aneurysm recanalization. The Analysis of Recanalization after Endovascular Treatment of intracranial Aneurysm (ARETA) study is a prospective multicenter cohort study evaluating the factors associated with recanalization after endovascular treatment. Methods: The current analysis is focused on patients treated by coiling or balloon-assisted coiling (BAC). Postoperative, mid-term vascular imaging, and evolution of aneurysm occlusion were independently evaluated by two neuroradiologists. A 3-grade scale was used for aneurysm occlusion (complete occlusion, neck remnant, and aneurysm remnant) and for occlusion evolution (improved, stable, and worsened). Recanalization was defined as any worsening of aneurysm occlusion. Results: Between December 2013 and May 2015, 16 French neurointerventional departments enrolled 1289 patients. A total of 945 aneurysms in 908 patients were treated with coiling or BAC. The overall rate of aneurysm recanalization at mid-term follow-up was 29.5% (95% CI 26.6% to 32.4%): 28.9% and 30.3% in the coiling and BAC groups, respectively. In multivariate analyses factors independently associated with recanalization were current smoking (36.6% in current smokers vs 24.5% in current non-smokers (OR 1.8 (95% CI 1.3 to 2.4); p=0.0001), ruptured status (31.9% in ruptured aneurysms vs 25.1% in unruptured (OR 1.5 (95% CI 1.1 to 2.1); p=0.006), aneurysm size ≥10 mm (48.8% vs 26.5% in aneurysms <10 mm (OR 2.6 (95% CI 1.8 to 3.9); p<0.0001), wide neck (32.1% vs 25.8% in narrow neck (OR 1.5 (95% CI 1.1 to 2.1); p=0.02), and MCA location (34.3% vs 28.3% in other locations (OR 1.5 (95% CI 1.0 to 2.1); p=0.04). Conclusions: Several factors are identified by the ARETA study as playing a role in aneurysm recanalization after coiling: current smoking, aneurysm status (ruptured), aneurysm size (≥10 mm), neck size (wide neck), and aneurysm location (middle cerebral artery). This finding has important consequences in clinical practice. Trial registration number: URL: http://www.clinicaltrials.gov ; Unique Identifier: NCT01942512 .